Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.